Therapeutic Potential of Exosomes in Pulmonary Fibrosis - Xie, Linshen; Zeng, Ye (Frontiers in Pharmacology, 2020)
Pulmonary fibrosis is closely associated with the recruitment of fibroblasts from capillary vessels with damaged endothelial cells, the epithelial mesenchymal transition (EMT) of type II alveolar epithelial cells, and the transformation of fibroblasts to myofibroblasts. Recent studies suggest that EMT is a key factor in the pathogenesis of pulmonary fibrosis, as the disruption of EMT-related effector molecules can inhibit the occurrence and development of PF. With the numerous advancements made in molecular biology in recent years, researchers have discovered that exosomes and their cargos, such as miRNAs, lncRNAs, and proteins, can promote or inhibit the EMT, modulate the transformation of fibroblasts into myofibroblasts, contribute to the proliferation of fibroblasts and promote immunoregulatory and mitochondrial damage during pulmonary fibrosis. Exosomes are key factors regulating the differentiation of bone marrow mesenchymal stem cells (BMSCs) into myofibroblasts. Interestingly, exosomes derived from BMSCs under pathological and physiological conditions may promote or inhibit the EMT of type II alveolar epithelial cells and the transformation of fibroblasts into myofibroblasts to regulate pulmonary fibrosis. Thus, exosomes may become a new direction in the study of drugs for the treatment of pulmonary fibrosis.